ANALYSIS OF BRAND IMAGE, SOCIAL MEDIA, AND VALUE PERCEPTION ON CONSUMER LOYALTY MEDIATED BY CONSUMER PREFERENCE FOR HEALTHY INSTANT NOODLE PRODUCTS - Sigma Prayitno Putri; Rina Sulistiyani; Bambang Raditya Purnomo (SOSIOEDUKASI, 2026)
The presence of healthy instant noodles in society addresses consumers’ needs for food that is easy to prepare while still paying attention to nutritional content, raw material quality, and production processes that are safer for health. The manufacturing process of healthy instant noodles that are baked rather than fried demonstrates the company’s commitment that the product is produced with attention to health aspects and food quality. Research related to consumer preference and loyalty through brand image, social media, and value perception factors was conducted on the Committee and Parents of Muhammadiyah 24 Surabaya Elementary School students with 172 respondents. Samples were taken using Purposive Sampling technique which emphasizes consumers aged over 18 years, who are Committee members and Parents of SD Muhammadiyah 24 Surabaya students, and have consumed healthy instant noodles at least 2 times to determine the level of loyalty possessed by consumers. The analysis technique used in this research is SEM-PLS, where after hypothesis testing, results showed that directly the variables of brand image, social media, and value perception have positive and significant effects on consumer preference. However, brand image and value perception do not have significant effects on loyalty. Additionally, consumer preference indirectly positively and significantly mediates the influence between brand image, social media, and value perception on consumer loyalty.